Brake Power Required to Avoid Vehicular Obstruction with a Steadfast Obstacle: A Probabilistic Approach - Suhir, Ephraim (Journal of Advances in Applied & Computational Mathematics, 2022)
A probabilistic approach is applied to assess the level of the available brake power needed to avoid obstruction with a steadfast obstacle suddenly detected in front of a moving vehicle. The obtained results can be used to establish, on the design stage, the level of this power for an extraordinary situation of the type in question and for an acceptable (in effect, never-zero) probability of an accident.